2019
DOI: 10.1007/978-3-030-05864-7_85
|View full text |Cite
|
Sign up to set email alerts
|

The Micro- and Macrostructure of Alumina Rafts

Abstract: As alumina particles are fed to aluminium reduction cells, a frozen layer of bath is typically formed on the particle surface, due to the relatively low bath superheat. For particles in close proximity, platelets with frozen bath can be formed, resulting in agglomerates (rafts) containing solidified bath and alumina. The formation, flotation and break up of these agglomerates is determined by macroscopic properties (i.e. size, density etc.) which in turn is related to microscopic properties, i.e. how grains ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The layered structure seen in figure 9b as been observed on anodes previously [2,3,10], but also on rafts [11], albeit with lower porosity and smaller pore size. As observed by Poncsak et al [10], the frozen bath is more compact close to the surface where it first freezes -i.e.…”
Section: Structure Of Frozen Layersupporting
confidence: 59%
“…The layered structure seen in figure 9b as been observed on anodes previously [2,3,10], but also on rafts [11], albeit with lower porosity and smaller pore size. As observed by Poncsak et al [10], the frozen bath is more compact close to the surface where it first freezes -i.e.…”
Section: Structure Of Frozen Layersupporting
confidence: 59%
“…The lower dissolution rate can be explained by increased bath freezing on the agglomerate, which also will result in a more rigid raft, less prone to disintegration and thus longer floating times -provided that the density of the raft is sufficiently low to keep it afloat -cf. [11].…”
Section: Discussionmentioning
confidence: 99%
“…The rafts were first cooled down on the skimming ladle before being removed and stored in vacuumed bags for further analysis, cf. [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of rafts have been intensified over the last years, and formation of rafts has been recorded in industrial cells [2], where bath circulations and temperature were found to affect the raft floating time, together with the moisture and fluoride content of the alumina. By extracting samples from the cell and further processing them by micro X-ray computed tomography (µCT) , it is revealed that the rafts are porous structures with an average density of 1.76 g/cm 3 and a porosity of 12.72% [3]. Earlier results by Walker et al [4] found the apparent density of collected agglomerates to be between 2.2 and 2.4 g/cm 3 and porosities between 24.7 and 22.8% in the time span of 15-60 s. However, both the sampling technique and characterization method is different, which might be the cause of the varying results.…”
Section: Introductionmentioning
confidence: 99%